New mothers' key questions about child vaccinations from pregnancy through toddlerhood: Evidence from a qualitative longitudinal study in Victoria, British, Columbia - Marian Orhierhor; Clara Rubincam; Devon Greyson; Julie A. Bettinger (Elsevier, 2023)
Canada's infant vaccination rate is suboptimal. British Columbia (BC) is below the targeted national coverage for infant vaccines, and vaccine hesitancy is a contributing factor in BC's low coverage rates. The literature suggests that many mothers are primary vaccine decision-makers and begin this decision process during pregnancy. This project examined mothers' vaccine concerns, vaccine information needs and preferences, and mother's trusted information sources regarding vaccines during early childhood.Using a qualitative, longitudinal design, interviews were conducted with women in four phases: during the third trimester of pregnancy, when the infant was 3-4 months, 9-12 months, and 15-18 months of age. Data analysis was thematic and both deductive and inductive coding techniques were utilized.Although most mothers in this study followed the BC infant vaccination schedule, many could be regarded as cautious acceptors. We identified five major themes. Three themes describe the questions mothers had about infant vaccination: 1) the vaccination schedule, 2) basic facts about vaccines, and 3) risks and benefits. Two themes described mothers' information sources and preferences: 1) information sources, and 2) vaccine information delivery. Mothers indicated they wanted their concerns to be addressed in a safe, non-judgmental environment by health care providers.The questions and concerns identified by mothers in this study suggest that many mothers have unasked and unanswered questions about infant vaccines. Because health care providers are the favored source of vaccine information for pregnant people and new parents, they should receive continuous education on vaccines to raise their competency in addressing parental concerns.